Zinc Regulates a Switch between Primary and Alternative S18 Ribosomal Proteins in Mycobacterium tuberculosis - Prisic, Sladjana (Mol Microbiol, 2015)
The Mycobacterium tuberculosis genome encodes five putative “alternative” ribosomal proteins whose expression is repressed at high Zn(2+) concentration. Each alternative protein has a primary homolog that is predicted to bind Zn(2+). We hypothesized that zinc triggers a switch between these paired homologous proteins and therefore chose one of these pairs, S18-1/S18-2, to study mechanisms of the predicted competition for their incorporation into ribosomes. As predicted, our data show that Zn(2+)-depletion causes accumulation of both S18-2 mRNA and protein. In contrast, S18-1 mRNA levels are unchanged to slightly elevated under Zn(2+)-limited conditions. However the amount of S18-1 protein is markedly decreased. We further demonstrate that both S18 proteins interact with ribosomal protein S6, a committed step in ribosome biogenesis. Zn(2+) is absolutely required for the S18-1/S6 interaction, while it is dispensable for S18-2/S6 dimer formation. These data suggest a model in which the S18-1 is the dominant ribosome constituent in high zinc conditions, e.g. inside of phagosomes, but that it can be replaced by S18-2 when zinc is deficient, e.g. in the extracellular milieu. Consequently, Zn(2+)-depletion may serve as a signal for building alternative ribosomes when M. tuberculosis is released from macrophages, to allow survival in the extracellular environment.